The Study on the Impact of the Account Age of Goodwill on Enterprise Value - L. Xiao (Chemical Engineering Transactions, 2015)
With the further development of economic globalization, the enterprise reorganization by merger andacquisition has increasingly become the important means of strategic development of many multinational companies. In many merger and acquisition cases happened around the world,the amount of goodwill accounts for the vast majority proportion in mergers and acquisitions. This study takes the Shanghai andShenzhen two city A-share listed companies from 2009 to 2012 as research samples, the empirical study exams the impact of the goodwill in general and goodwill with the different account-age on the enterprise value. The study found that goodwill has the significant positive correlation with enterprise value in general. The impact of goodwill obtained in current year, one year and two year earlier respective on the share price gradually increased, but the correlation between goodwill with more than three years earlier and share price dropped significantly.